2008
DOI: 10.1002/ibd.20409
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pouch failure in patients with different phenotypes of Crohnʼs disease of the pouch

Abstract: Younger age, being an ex-smoker, and the requirement for immunomodulators or biologics were associated with pouch failure. The identification of these risk factors may help delineate the natural history of CD of the pouch and shed light on proper clinical management and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 32 publications
0
37
1
2
Order By: Relevance
“…Within the CDL group, 56.6% were diagnosed based on the presence of a fistula or abscess developing more than 1 year after surgery, 36.4% based on inflammation extending into the afferent limb and 7.0% met both criteria. Factors previously related to pouch outcome such as smoking and family history of IBD10 12 were not found to be significantly associated in this cohort. However, the presence of large-joint arthritis (p=0.02) and PSC (p=0.009) were significantly associated with both the CP and CDL outcomes.…”
Section: Resultscontrasting
confidence: 60%
“…Within the CDL group, 56.6% were diagnosed based on the presence of a fistula or abscess developing more than 1 year after surgery, 36.4% based on inflammation extending into the afferent limb and 7.0% met both criteria. Factors previously related to pouch outcome such as smoking and family history of IBD10 12 were not found to be significantly associated in this cohort. However, the presence of large-joint arthritis (p=0.02) and PSC (p=0.009) were significantly associated with both the CP and CDL outcomes.…”
Section: Resultscontrasting
confidence: 60%
“…Symptoms might resolve after a defined treatment course with broad-spectrum antibiotics; however, some cases require continuous therapy, immunomodulators, or biologics to maintain symptom control. 7 Up to 20% of patients with a pouch go on to develop a Crohn's disease (CD)-like (CDL) phenotype, characterized by inflammation in the afferent limb, the presence of proximal small bowel strictures unrelated to surgery, or perianal/abdominal fistulas or abscesses that occur at a remote time from the IPAA procedure. [7][8][9] Prior studies have identified factors that might be associated with inflammatory complications of the ileal pouch in inflammatory bowel disease (IBD) such as smoking, colonic disease extent, primary sclerosing cholangitis (PSC), and extraintestinal manifestations.…”
mentioning
confidence: 99%
“…the present study was conceived to evaluate surgical variables as well as other factors associated with the fate of an ileal pouch complicated by de novo CD after iPaa, which is a major cause of pouch failure. When assessing a patient cohort selected from our institutional Pouchitis Registry, shen et al 14 reported that younger age, former smoker status, and the requirement for immunomodulator therapy or biologics were independently associated with an increased risk of pouch failure. the same group from our institution also reported that patients with fistulizing disease phenotype demonstrated a trend toward worse pouch survival, which nearly approached statistical significance.…”
Section: Discussionmentioning
confidence: 98%